Measure of agreement between experts on apple damage assessment - Vincent, C.; Hanley, J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
Although damage evaluation is an important and frequent exercise in economic entomology, there are no quantitative studies on inter-rater agreement of experts. In this experiment conducted during the 50th New York, New England and Canadian Pest Management Conference, four teams of experts independently estimated the damage on 200 apples at harvest. The participants identified 22 types of damage caused by insects, 8 by diseases, and 8 related to other causes. For each type of damage an average measure of agreement was calculated. The lowest average agreements were found in plum curculio (Conotrachelus nenuphar) [Coleoptera : Curculionidae] damage (71.8%), tarnished plant bug (Lygus lineolaris) [Hemiptera : Miridae] damage (83.2%), and by early lepidoptera damage (87.1%). The usefulness of inter-rater agreement experiments is discussed in the context of many situations pertaining to crop protection.